Mental Health Outcomes of Discrimination among College Students on a Predominately White Campus: A Prospective Study. (May 2019) - Jochman, Joseph C.; Cheadle, Jacob E.; Goosby, Bridget J.; Tomaso, Cara; Kozikowski, Chelsea; Nelson, Timothy
Racial discrimination is a social stressor harmful to mental health. In this paper, we explore the links between mental health and interpersonal discrimination-related social events, exposure to vicarious racism via social media, and rumination on racial injustices using a daily diary design. We utilize data from a racially diverse sample of 149 college students with 1, 489 unique time observations at a large, predominantly white university. Results show that interpersonal discrimination-related social events predicted greater self-reported anger, anxiety, depressive symptoms, and loneliness both daily and on average over time. Vicarious racism from day to day was associated with increased anxiety symptoms. In contrast, rumination was not associated with negative mental health outcomes. These findings document an increased day-to-day mental health burden for minority students arising from frustrating and alienating social encounters experienced individually or learned about vicariously.